Potential Development of SRI Sukuk Models for Higher Learning Institutions in Malaysia based on Wakalah and Waqf - Engku Rabiah Adawiah Engku Ali; Syed Marwan Mujahid Syed Azman; Nor Razinah Mohd Zain; Rusni Hassan; Salina Kassim (Journal of Islamic Finance, 2019)
Funding for Higher Learning Institutions (HLIs) in Malaysia has become increasingly constrained as the government faces increasing costs and global economic slowdown. Central to this issue is the challenge to raise the funds needed to sustain HLIs’ operations and development. It has therefore become a necessity for HLIs to come up with innovative ways to raise funds and move towards to becoming more self-sustainable. Malaysia can possibly learn from HLIs in the UK, US, and Australia where universities have managed to obtain funds through the capital market by issuing bonds. This paper focuses on exploring alternative financing modes for HLIs through Socially Responsible Investment (SRI) sukuk and Social Impact Bonds (SIBs). The methods utilized in this study are critical review of literature, case study analyses and interview sessions with experts. This study recommends two SRI sukuk models: firstly, in the situation where the proceeds are used for income-generating activities, sukuk based on wakalah is proposed; while secondly for non-income generating activities, a cash-waqf sukuk with temporary and permanent features is suggested. In term of the structure of the sukuk, the returns and repayments of both sukuk are dependent on key performance indicators (KPIs) being achieved. In both cases, it is recommended that the sukuk be issued by a consortium consisting of a number of different universities in order to lower the cost of issuance and fund management, as well as efficiently utilizing resources. It is also recommended that the sukuk is guaranteed by a third party, preferably by the government.